PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION SEBAGAI UPAYA PENINGKATAN KETERAMPILAN MENGAMATI PADA MATERI TEMA 3 BENDA DISEKITARKU SISWA KELAS III SDN 20 CAKRANEGARA - NI LUH SRI MURNIATI (GANEC SWARA, 2019)
This Classroom Action Research (CAR) was conducted at SDN 20 Cakranegara with the aim of increasing the value of students' skills, especially in the theme material 3 Objects around me through the use of a cooperative learning approach Type Group Investigation (GI).     The type of research used is Classroom Action Research which consists of planning, implementation, observation, and reflection. The subjects of this study were 44 grade students of SDN 20 Cakranegara. PTK is carried out in two cycles. Cycle I consists of 3 meetings and cycle II consists of 2 meetings. The action in this study was to use a cooperative learning model type Group Investigation (GI). The value of student skills is obtained during the learning process in the form of performance appraisal at each meeting. Furthermore, the collected data were analyzed descriptively quantitatively.     From the results of data analysis, it was found that the achievement of the skills of students in the first cycle was as follows; of 44 students as many as 34 students (77.27%) who obtained a value of ≥70 and as many as 10 people (20.73%) had not reached the value of ≥70. The average skill score of students in cycle I is 70.80. Cycle II of 44 students as many as 40 students (90.91%) who obtained a value of ≥70 and as many as 4 people (9.09%) had not reached the value of ≥70. The average skill score of the second cycle students is 86.70. The determined performance indicator is 85% of students obtain a skill score of ≥70 with the Good category. Thus it can be concluded that the cooperative learning model of the Group Investigation type can increase the value of the skills of third grade students of SDN 20 Cakranegara.